Workload and Work Stress in Affecting Employee Performance - Simon Siamsa,; Adrianus Aprilius, (Technium Social Sciences Journal, 2023)
The primary objective of this research is to examine how the amount of work and stress experienced on the job impact the overall performance of employees working at BPJS Merauke. This investigation employs a quantitative approach. The sampling method utilized is Total Sampling, involving all 31 employees in the BPJS Merauke branch. Data collection encompasses questionnaires, interviews, and observations. The collected data is processed through the utilization of SPSS version 25, using the technique of multiple regression analysis. The findings of the study reveal that the workload significantly influences employee performance at BPJS Merauke, as evidenced by the computed t-value of 4.455, surpassing the critical t-table value of 2.048. Additionally, the p-value of 0.000, which is less than the significance level of 0.05, strengthens this significance. Furthermore, the impact of work stress on employee performance is also substantial. This is substantiated by the t-value of 3.232, exceeding the critical t-table value of 2.048. The associated p-value of 0.003, which is lower than the 0.05 significance level, further underscores the significance of this relationship.